Unlocking Precision: Inorganic Nanoparticles Sparking the Next Revolution in Cancer Theranostics - Sivakumar, Sudesh; Sambasivam, Dhinesh Kumar; Krishnan, Suresh Kumar (Indian Journal of Pharmacy Practice)
Nanotechnology has profoundly transformed Drug Delivery Systems (DDS), with Inorganic Nanoparticles (INPs) emerging as promising and versatile carriers owing to their exceptional stability, tunable size, and unique physicochemical properties. This review highlights the pivotal role of INPs-such as Gold Nanoparticles (AuNPs), Mesoporous Silica Nanoparticles (MSNs), and Superparamagnetic Iron Oxide Nanoparticles (SPIONs)-in theranostics, a cutting-edge approach that integrates diagnosis and therapy within a single nanosystem. INPs have demonstrated remarkable potential across diverse biomedical applications: AuNPs and SPIONs are extensively employed in Photothermal Therapy (PTT) and magnetic resonance Imaging (MRI) contrast enhancement for cancer, Silver Nanoparticles (AgNPs) exhibit potent antimicrobial activity, and Cerium Oxide Nanoparticles (CeO₂ NPs) offer neuroprotective benefits. In oncology, these nanocarriers overcome multidrug resistance, facilitate RNA interference (RNAi)-based treatments, and exploit the Enhanced Permeability and Retention (EPR) effect for passive tumor targeting. Notable advancements include the use of AuNPs for precise PTT and Hafnium Oxide Nanoparticles (HfO₂ NPs) as effective radiosensitizers. Despite significant progress, challenges such as long-term biocompatibility, rapid clearance by the Reticuloendothelial System (RES), and scalability limitations hinder clinical translation. Future directions emphasize the design of stimuli-responsive and multifunctional nanoplatforms that actively modulate the tumor microenvironment, integrate immunotherapeutic strategies, and enable personalized, precision-driven cancer treatment.
Keywords: Cancer Theranostics; Drug Delivery Systems; EPR Effect; Immunotherapy; Inorganic; Nanoparticles; MRI Contrast Agents; Photothermal Therapy; Stimuli-Responsive Nanomedicine; Tumor Microenvironment